The cellular function of srGAP3 and its role in neuronal morphogenesis - Bacon, Claire; Endris, Volker; Rappold, Gudrun (Mechanisms of development, 2013)
The Slit-Robo GTPase activating protein 3 (srGAP3) dynamically regulates cytoskeletal reorganisation through inhibition of the Rho GTPase Rac1 and interaction with actin remodelling proteins. SrGAP3-mediated reorganisation of the actin cytoskeleton is crucial for the normal development of dendritic spines and loss of srGAP3 leads to abnormal synaptic activity and impaired cognitive behaviours in mice, which is reminiscent of an association between disrupted srGAP3 and intellectual disability in humans. Additionally, srGAP3 has been implicated to act downstream of Slit-Robo signalling in commissural axons of the spinal cord. Thus, srGAP3-mediated cytoskeletal reorganisation has an important influence on a variety of neurodevelopmental processes, which may be required for normal cognitive function.